A Novel NAD Signaling Mechanism in Axon Degeneration and its Relationship to Innate Immunity - Hopkins, Eleanor L.; Gu, Weixi; Kobe, Bostjan; Coleman, Michael P. (Frontiers in Molecular Biosciences, 2021)
Axon degeneration represents a pathological feature of many neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease where axons die before the neuronal soma, and axonopathies, such as Charcot-Marie-Tooth disease and hereditary spastic paraplegia. Over the last two decades, it is slowly emerging that the central signaling pathway that forms the basis of this process in many circumstances is an axonal NAD-related signaling mechanism, mainly regulated by the two key proteins with opposing roles, the NAD synthesizing enzyme NMNAT2 and SARM1, a protein with NADase and related activities. The crosstalk between the axon survival factor NMNAT2 and pro-degenerative factor SARM1 has been extensively characterized and plays an essential role in maintaining the axon integrity; and this pathway can be activated in genetic, toxic and metabolic disorders in addition to physical injury, leading to axon pathology. SARM1 is also known to be involved in regulating innate immunity, potentially linking axon degeneration to the response to pathogens and intercellular signaling. Understanding this NAD-related signaling mechanism enhances our understanding of the process of axon degeneration and enables a path to the development of drugs for a wide range of neurodegenerative diseases.